2018
DOI: 10.3390/app8122696
|View full text |Cite
|
Sign up to set email alerts
|

Impregnation of Wood with Microencapsulated Bio-Based Phase Change Materials for High Thermal Mass Engineered Wood Flooring

Abstract: Wood is a porous material that can be impregnated and have enhanced properties. Two species of hardwood, red oak (Quercus rubra L.) and sugar maple (Acer saccharum Marsh.), were impregnated in a reactor with a microencapsulated phase change material. The objective was to enhance the thermal mass of wood boards used as surface layers for engineered wood flooring manufacturing. Preliminary experiments were conducted on small samples in order to define suitable impregnation parameters, based on the Bethell cycle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…This panel consists of three layers including an MDF and a high-density fiberboard (HDF) panel, as well as a plastic bag of PCM ( Figure 1) [54]. The properties of the functional units are listed in Table 1 [54,55]. Figure 1.…”
Section: Pcm Panelmentioning
confidence: 99%
See 1 more Smart Citation
“…This panel consists of three layers including an MDF and a high-density fiberboard (HDF) panel, as well as a plastic bag of PCM ( Figure 1) [54]. The properties of the functional units are listed in Table 1 [54,55]. Figure 1.…”
Section: Pcm Panelmentioning
confidence: 99%
“…The properties of the functional units are listed in Table 1 [54,55]. [10], which is an international standard framework for conducting LCAs.…”
Section: Pcm Panelmentioning
confidence: 99%
“…The melting and cooling temperature of TES-WPC were 27.2 and 11.3 C, respectively, which indicated that the supercooling was negative for its application. Mathis et al 35 selected red oak (Quercus rubra L.) and sugar maple (Acer saccharum Marsh.) as the base materials to prepare TES wood.…”
Section: Introductionmentioning
confidence: 99%
“…The application of microcapsules to wood can generally be carried out through the impregnation treatment of microcapsule suspension into the pores of the wood [ 13 ], the physical mixing of microcapsules and adhesives into human-made boards [ 14 ], and the addition of microcapsules to the coating in advance through coating treatment [ 15 ]. But from the perspective of industrial production and “dynamic” color change decoration, the use of impregnation and adhesive may lead to problems such as high cost and large energy requirements, as well as uncertainty as to whether the microcapsules will maintain their shape and properties under heating and compressive stress [ 16 ].…”
Section: Introductionmentioning
confidence: 99%